Modifikasi Aritmatika Aljabar pada Bilangan Fuzzy Hexagonal dan Penentuan Invers Matriks - Ayu Puspita, Dian; Mashadi, Mashadi (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2025)
Hexagonal fuzzy numbers are a development of trapezoidal fuzzy numbers. Just like algebra for trapezoidal fuzzy numbers. There are not many algebraic differences given by various authors for the many operations of addition, subtraction, and scalar multiplication.  However, for multiplication, division, and inverse operations, there are many algebraic alternatives offered by various authors in parametric and ordinary forms. But the problems that arise do not always have an inverse for any hexagonal fuzzy number  . In this paper, by changing hexagonal fuzzy numbers into another form  and defining two midpoints  and  for any hexagonal fuzzy number . Thus, for the algebraic forms of multiplication, division, and inverse there is one that is produced  using the elementary row method. At the end, an example of determining the inverse of a hexagonal fuzzy number matrix that has order .  Keywords: Algebra arithmetic, hexagonal fuzzy number, inverse matrix